(untitled) (KULT_online, 2009)
The Persistence of Myth as Symbolic Form collects papers from an international conference organised by the Centre for Intercultural Studies at the University of Glasgow (16-18.9.2005). The volume, edited by Paul Bishop and Roger H. Stephenson, explores the potential of Ernst Cassirer’s concept of myth for contemporary issues in cultural theory and investigates the scope of influences essential to his thinking. Drawing from philosophical, historical, anthropological, literary, aesthetic, scientific and political perspectives, the authors home in on the central question: in what ways can knowledge productively address the irrefutable power of myth?